Body coloration and mechanisms of colour production in Archelosauria: the case of deirocheline turtles. Issue 7 (24th July 2019) - Brejcha, Jindřich; Bataller, José Vicente; Bosáková, Zuzana; Geryk, Jan; Havlíková, Martina; Kleisner, Karel; Maršík, Petr; Font, Enrique
Abstract : Animal body coloration is a complex trait resulting from the interplay of multiple mechanisms. While many studies address the functions of animal coloration, the mechanisms of colour production still remain unknown in most taxa. Here we compare reflectance spectra, cellular, ultra- and nano-structure of colour-producing elements, and pigment types in two freshwater turtles with contrasting courtship behaviour, Trachemys scripta and Pseudemys concinna . The two species differ in the distribution of pigment cell-types and in pigment diversity. We found xanthophores, melanocytes, abundant iridophores and dermal collagen fibres in stripes of both species. The yellow chin and forelimb stripes of both P. concinna and T. scripta contain xanthophores and iridophores, but the post-orbital regions of the two species differ in cell-type distribution. The yellow post-orbital region of P. concinna contains both xanthophores and iridophores, while T. scripta has only xanthophores in the yellow-red postorbital/zygomatic regions. Moreover, in both species, the xanthophores colouring the yellow-red skin contain carotenoids, pterins and riboflavin, but T. scripta has a higher diversity of pigments than P. concinna . Trachemys s. elegans is sexually dichromatic. Differences in the distribution of pigment cell types across body regions in the two species may be related to visual signalling but do not match predictions based on courtship position. Our results demonstrate that archelosaurs share some colour production mechanisms with amphibians and lepidosaurs (i.e. vertical layering/stacking of different pigment cell types and interplay of carotenoids and pterins), but also employ novel mechanisms (i.e. nano-organization of dermal collagen) shared with mammals.